'Why has my world become more confusing than it used to be?' Professional doctoral students reflect on the development of their identity. (October 2015) - Rayner, Stephen; Lord, Janet; Parr, Elizabeth; Sharkey, Rachel
This article reports on research into the experience of professional doctoral students and is written by the students themselves. We, the authors, are currently studying for the Doctorate in Education at the University of Manchester, UK. We place our work in the context of recent empirical research into the development of doctoral student identity, noting that these literatures are usually authored by programme directors and supervisors. Using a theoretical approach based on the work of Etienne Wenger, we examine how the aims and curriculum of our programme interplay with our professional learning. In interviews with our cohort of students, we explore the complexity and non-linearity of learning. We do not find a simple progression from practitioner to researcher; rather, we find a fluid and complex relationship between those two identities. We consider the extent to which Wenger's modes of identification are a useful conceptual tool for understanding this interplay and for theorising about our findings. We conclude that there is further scope for the development of our theoretical framework by drawing on other scholarly work on identity development and reflexivity.